2016
DOI: 10.1111/ics.12352
|View full text |Cite
|
Sign up to set email alerts
|

Sensory analysis of cosmetic powders: personal care ingredients and emulsions

Abstract: The lexicon developed in this study can be used for assessment of other powders but also to define the quantities necessary to put in the formulation to meet the sensory characteristics of these raw materials powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Moussour et al . reported that the required powders used in colour cosmetic formulations are increasing dramatically because of the sensory benefits provided. Sensory profile of a formulation can be greatly altered by incorporating powders such as talc, mica and pigments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moussour et al . reported that the required powders used in colour cosmetic formulations are increasing dramatically because of the sensory benefits provided. Sensory profile of a formulation can be greatly altered by incorporating powders such as talc, mica and pigments.…”
Section: Introductionmentioning
confidence: 99%
“…According to Azmi Hassali et al [1], the eye colour cosmetic market's total import value in the United States in 2013 was 20.6 million USD, and the powder make up market's import value in 2013 was 20.2 million USD. Moussour et al [2] reported that the required powders used in colour cosmetic formulations are increasing dramatically because of the sensory benefits provided. Sensory profile of a formulation can be greatly altered by incorporating powders such as talc, mica and pigments.…”
Section: Introductionmentioning
confidence: 99%
“…A lower number of articles have been published concerning the cosmetic powder. Those which did have highlighted some sensory attributes, such as softness, slipperiness and cushioning, characteristics of this product universe .…”
Section: Introductionmentioning
confidence: 99%
“…Powder ingredients are widely used in cosmetics as main constituents in loose (flow) and compact (pressed) powder make‐up [1, 2], where they may provide adhesiveness, smoothness, absorbency, coverage, or different sensory or visual attributes to skin and hair [3]. Powder ingredients are also commonly used in liquid formulations in which they can improve the look, feel, cohesion, viscosity or texture of the formulations.…”
Section: Introductionmentioning
confidence: 99%